Targeted temperature management after cardiac arrest: the longer, the better? - Bougouin, Wulfran; Lascarrou, Jean-Baptiste; Dumas, Florence; Cariou, Alain (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Despite recent improvements in their management, the prognosis of patients resuscitated from an out-of-hospital cardiac arrest (OHCA) remains poor, as reflected by a very high mortality rate (1-3). In patients in whom a return of spontaneous circulation (ROSC) has been obtained due to cardiopulmonary resuscitation (CPR), many subsequent deaths are observed during the following days and weeks, most of these deaths resulting from anoxic-ischemic brain damages (4).